Clinical Study of Autonomic Dysfunction in Patients With Anti-NMDA Receptor Encephalitis - Yan, Lulu; Zhang, Shuang; Huang, Xiaoxue; Tang, Yao; Wu, Jun (Frontiers in Neurology, 2021)
Objectives: Autonomic dysfunction is a common symptom of anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis; however, it has been poorly researched. The purpose of this study was to compare the clinical features, tumor occurrence, intensive care unit (ICU) admission, mechanical ventilation, imaging assessment, cerebrospinal fluid examination, disease severity, and immunotherapy in patients with anti-NMDAR encephalitis with or without autonomic dysfunction. Methods: A retrospective study of anti-NMDAR encephalitis patients diagnosed between January 2016 and April 2020 was performed at the First Affiliated Hospital of Zhengzhou University. Patients were divided into two groups according to whether they had autonomic dysfunction, and their clinical features, treatment, and prognosis were compared. Results: A total of 119 patients with anti-NMDAR encephalitis were included in this study. Seventy-three patients (61.3%) had autonomic dysfunction, while the remaining 46 (38.7%) did not. Sinus tachycardia (69.9%) was the autonomic dysfunction with the highest incidence, while the incidences of symptoms including constipation, central hypopnea, and others gradually decreased. Compared to the group without autonomic dysfunction, the prevalence of the main clinical symptoms such as epileptic seizure (P=0.003), involuntary movement (P = 0.028), and decreased consciousness (P＜0.001) were higher in the group with autonomic dysfunction, which also more frequently presented with complications such as pulmonary infection (P＜0.001) and abnormal liver function (P=0.001). Moreover, the rates of ICU admission (P＜0.001) and mechanical ventilation (P=0.001), as well as the modified Rankin scale (mRS) scores at admission (P＜0.001), maximum mRS scores during the course of disease (P＜0.001), and mRS scores at discharge (P＜0.001) were higher in the patients with autonomic dysfunction than in those without. The number of patients in the autonomic dysfunction group who underwent ≥2 immunotherapies was also higher than that in the group without autonomic dysfunction (P＜0.001). Conclusion: Sinus tachycardia is the most common type of autonomic dysfunction in anti-NMDAR encephalitis. Compared to patients without autonomic dysfunction, those with autonomic dysfunction had a higher incidence of epilepsy, involuntary movements, decreased consciousness, pulmonary infections, abnormal liver function, ICU admissions, and mechanical ventilation; moreover, the severity of the disease was greater, and their prognosis worse. Therefore, such patients require intensive immunotherapy.